OPTIMASI PENENTUAN TINGKAT PENGADAAN BAHAN BAKU PADA USAHA MICRO KECIL MENENGAH - Simorangkir, Parulian; Citra Indah Asmarawati (Computer Science and Industrial Engineering, 2024)
This research aims to determine the control of the supply of soybean raw materials applied to Tahu Saguba MSMEs. The data processed is data on supplies, purchases and use of soybean raw materials at Tahu Saguba MSMEs from June 2023 to May 2024, using the Economic Order Quantity (EOQ) method. The research results are as follows: the number of orders for soybean raw materials is 145 sacks, the frequency of orders is 18 times, the safety stock is 14 sacks, ROP can be carried out when the soybean raw materials are in the warehouse as many as 22 sacks, with a total inventory cost of IDR 1,074,989 . The conclusion of this research shows that the application of the Economic Order Quantity (EOQ) method shows a more optimal order quantity compared to the method currently used by MSME Tahu Saguba